1987
DOI: 10.1093/carcin/8.11.1635
|View full text |Cite
|
Sign up to set email alerts
|

Combination experiments with very low doses of three genotoxic N-nitrosamines with similar organotropic carcinogenidty in rats

Abstract: The study was designed to assess the syncarcinogenic activity of very low doses of N-nitrosodiethylamine (NDEA), N-nitrosopyrrolidine (NPYR) and N-nitrosodiethanolamine (NDElA) in the liver of 1800 male Sprague-Dawley rats. The N-nitrosamines were administered throughout the rats' lives individually and in combination at three logarithmically spaced dose levels contained in drinking water. The dose levels in the individual dose-response experiments ranged from the lowest concentrations of previous experiments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 0 publications
1
26
0
Order By: Relevance
“…However, at low dose levels, this is not always the case; thus significant findings were that a low dose combination of three carcinogenic nitrosamines did not e x e r t s u m m a t i o n o r s y n e r g i s m r e g a r d i n g t u m o r development 10 , and a combination of 20 or 40 pesticides at A D I l e v e l s r e s u l t e d i n n o e n h a n c e m e n t o f hepatocarcinogenesis, but at doses at the NOEL, removing the safety factor of ×100, synergistic enhancement of GST-P positive foci was demonstrated 21 . From the theoretical point of view, the safety factor reflects both the possibility of an increased sensitivity of humans relative to laboratory animals and the variation in susceptibility within the human population, and that for ADI used by the Japanese Ministry of Health, Labour and Welfare and the FAO/WHO is usually 100.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, at low dose levels, this is not always the case; thus significant findings were that a low dose combination of three carcinogenic nitrosamines did not e x e r t s u m m a t i o n o r s y n e r g i s m r e g a r d i n g t u m o r development 10 , and a combination of 20 or 40 pesticides at A D I l e v e l s r e s u l t e d i n n o e n h a n c e m e n t o f hepatocarcinogenesis, but at doses at the NOEL, removing the safety factor of ×100, synergistic enhancement of GST-P positive foci was demonstrated 21 . From the theoretical point of view, the safety factor reflects both the possibility of an increased sensitivity of humans relative to laboratory animals and the variation in susceptibility within the human population, and that for ADI used by the Japanese Ministry of Health, Labour and Welfare and the FAO/WHO is usually 100.…”
Section: Discussionmentioning
confidence: 99%
“…Berger et al 10 For combination studies, three different dose levels were set, the high dose combination being composed of the middle doses of individual carcinogens, the middle dose combination being constituted by the lowest doses of each given individually and the low dose combination consisting of one-third of each of the lowest doses. They found that all carcinogens individually as well as in combination induced liver cancers in a dose-dependent manner.…”
Section: Combinations Of Very Low Doses Of Carcinogensmentioning
confidence: 99%
“…For example, in vitro genotoxicity studies on N-nitrosodiphenylamine [CAS: 86±30±6] were inconclusive or negative (McGregor 1994) with the exception of one study, where microcolony induction in S. typhimurium TA104 was observed in the presence of arochlor-1254 induced S9 at pH 6.5 (Zielenska and Guttenplan 1988). The potent experimental carcinogen N-nitrosopyrrolidine (Berger et al 1987) can only be eectively activated to Ames test positive metabolites by pyrazole-induced rat liver S9 (Burke et al 1994). Pyrazole is known to induce CYP2E1 in rat liver.…”
Section: Discussionmentioning
confidence: 99%
“…The TD5o, our numerical index of carcinogenic potency, has been fully described (1,5,6) and may be briefly defined as follows: Fora given target site(s), if there are no tumors in control animals, then TDso is the chronic dose rate in mg/kg body weight/day that would induce tumors in half the test animals at the end of a standard lifespan for the species. Because the tumor(s) of interest often does occur in control animals, TD5o is more precisely defined as the chronic dose rate that will halve the probability of remaining tumor-free throughout the standard life span.…”
Section: Introductionmentioning
confidence: 99%
“…(carcinogenic potency) and its statistial significance, dose response, author's opinion about carcinogenicity, and literature citation. We refer the reader to the 1984 publications (1,5,6) for a guide to the plot of the database, a complete description of the numerical index ofcarcinogenic potency, and a discussion ofthe sources of data, the rationale for the inclusion of particular experiments and particular target sites, and the conventions adopted in summarizing the literature. The five plots of the database are to be used together, as results ofindividual experiments that were published earlier are not repeated.…”
mentioning
confidence: 99%